Black Hole or Living Hall: Reconstructing Female Sexuality, Deconstructing Male Anxiety - ÖMÜR, GİZEM SERDAR (İstanbul Kültür Üniversitesi, 2022)
In this study, the main concern is to apply a reconstructive approach to reshape the image of female genitalia by restoring a primordial representation of women. To achieve this, I delve into multiple disciplines once amalgamated by androcentric forces that debilitated women, with an intent of reverting the same perception for the benefit of women by activating such primordial images of women. Instead of the priority given to death and destruction in defining and contemplating the meaning of life, as observed in the present phallocentric systems, this study provides a new understanding arising from female genitals from which life emerges and to which all living beings yearn to return as nostalgia and 'a belated wish' as Freud says. Concentrating on the representation of female sexuality in American cartoonist Charles Burns' graphic novel Black Hole, British writer Angela Carter's The Passion of New Eve and German writer Patrick Süskind's Perfume, this M.A. thesis employs several contemporary and interdisciplinary theories and methodologies to decode and recode the symbols, images, figures and metaphors attributed to women in cultural history. In this regard, placing the aforementioned literary works in their specific contexts and taking them under scrutiny in their attempt to cross the borders that western logocentrism dictates, this study suggests a thorough analysis of the distaff side, the underwritten part of history. This analysis is essential in that it aims to revive the repressed image of a Goddess figure, who 'creates the world by dancing', and asks for recognition by way of substitutions as they appear in the form of 'objet petit a', 'uncanny', 'abject', 'grotesque'; euphemistically called 'black hole' and 'black continent'. The sum of such concepts connotes monstrous, a non-human other in patriarchal discourse. However, such a view also assigns women to an in- between state of animate/inanimate, animal/human, female/male, defying the western binarised philosophy towards a nonbinary understanding. Therefore, this study concludes that the monstrosity attached to the female reproductive body through various ways, alongside the major anxiety that has governed the male economy for thousands of years, arises from a deathly attraction, as displayed by the keen analysis of the given three literary texts in the light of Irigaray's multiplicity and fluidity, fed by Cixous's aphorisms, supported by Kristeva's 'chora' and Ettinger's 'matrixial', manifested in Eisler's prehistoric Goddess figurines and Creed's 'monstrous feminine'.
Kara Delik Ya Da Yaşam Odası: Kadın Cinselliğini Yeniden Yapılandırılması, Erkek Anksiyetesinin Yapısökümü
▪ Yüksek lisans tezi.
Keywords: Reconstruction; Black Hole; Primordial; Procreational; Female Genitals; Attraction; Pleasure; Non-binary; Monstrosity; Repressed; Nostalgia; Abject; Uncanny; Grotesque; Disgust; Home; Charles Burns; Angela Carter; The Passion of New Eve; Patrick Süskind; Perfume: The Story of a Murderer